HIGHER MICRORNA-132 IS ASSOCIATED WITH BLOOD PRESSURE AND LIVER STEATOSIS IN OBESE INDIVIDUALS. (June 2018) - Eikelis, N.; Dixon, J.; Lambert, E.; Hanin, G.; Greenberg, D.; Soreq, H.; Marques, F.; Schlaich, M.; Lambert, G.
Abstract : Objective: Obesity is associated with numerous comorbidities including cardiovascular disease, diabetes and non-alcoholic fatty liver disease (NAFLD). Obesity pathogenesis is complex and incompletely understood and hence therapeutic options to address the global epidemic of obesity are lacking. In addition, NAFLD is strongly linked to cardiovascular disease. Our recent findings in experimental models have shown that microRNA miR-132 is an important regulator of liver homeostasis. Here, we aimed to assess miR-132 expression in liver and fat tissue of obese individuals and its association with blood pressure and hepatic steatosis. Design and method: Obese individuals undergoing bariatric surgery for weight management (n = 14 females/5 males) comprised the cohort of this study. They were 39 ± 2 years old (mean ± SEM) with a body mass index (BMI) of 42 ± 1 kg/m2. Extensive clinical and demographic information was collected for each patient. Supine blood pressure, measured with Omron HEM-907 device, was on average 127 ± 4 mmHg (systolic) and 74 ± 2 mmHg (diastolic) and heart rate 67 ± 24 beats/min. According to Adult Treatment Panel III, the participants had 2.2 ± 0.3 metabolic abnormalities. Quantitative PCR was performed to determine tissue expression of miR-132 in liver and matched subcutaneous and visceral fat biopsies in these patients. Liver biopsies were read by a single hepatopathologist using a standardised pathological approach and graded in terms of steatosis, inflammation and fibrosis. Results: Hepatic and visceral fat expression of miR-132 were strongly correlated (r = 0.729, P = 0.005). Hepatic miR-132 expression was also correlated with BMI (r = 0.641, P = 0.018), triglycerides (r = 0.604, P = 0.029), systolic blood pressure (r = 0.577, P = 0.039) and heart rate (r = 0.694, P = 0.009). Visceral fat miR-132 expression was associated with BMI (r = 0.746, P < 0.001) and liver steatosis (r = 0.533, P = 0.33). There was no correlation between subcutaneous and visceral expression of miR-132 (P = 0.210). Conclusions: Our data supports that miR-132 may play a causal role in the cardiovascular and metabolic implications of obesity in humans. Given the increasing public burden of obesity and associated comorbidities, novel therapeutic approaches are needed for prevention and treatment of these diseases. In addition, further targeted search for biomarkers in complex diseases such as obesity, cardiovascular disease and NAFLD are warranted.